An Examination of Community Awareness and Understanding of Patron Banning Provisions in Western Australia: Implications for Policy Development and Success - Farmer, Clare (European journal on criminal policy and research, 2024)
Individuals who engage in problematic behaviours within Australian night-time entertainment precincts can be banned from entering certain locations. Bans are expected to deter recipients and the wider community from further inappropriate behaviours. The collective effect is intended to reduce crime and increase safety within entertainment precincts. This study examined public awareness and understanding of two patron banning mechanisms (police barring notices and prohibition orders) used across Western Australia (WA). An anonymous survey was completed by 1018 respondents, and interviews were conducted with 54 stakeholders. Survey participants had limited awareness of patron banning: 75% had not heard of police barring notices; 87% had not heard of prohibition orders. Knowledge was higher for individuals directly associated with a ban recipient. Stakeholders also perceived a low level of community awareness and understanding of patron banning. Patron banning may have some merit as a specific deterrent for recipients but, in WA, the lack of public knowledge means that the banning provisions may currently have limited effect as a general deterrent. Public awareness should be increased in order to optimise the direct and consequential effects of patron banning policy.